Phase transitions in Thirring's model. (14th July 2016) - Campa, Alessandro; Casetti, Lapo; Latella, Ivan; Pérez-Madrid, Agustín; Ruffo, Stefano
Abstract: In his pioneering work on negative specific heat, Walter Thirring introduced a model that is solvable in the microcanonical ensemble. Here, we give a complete description of the phase-diagram of this model in both the microcanonical and the canonical ensemble, highlighting the main features of ensemble inequivalence. In both ensembles, we find a line of first-order phase transitions which ends in a critical point. However, neither the line nor the point have the same location in the phase-diagram of the two ensembles. We also show that the microcanonical and canonical critical points can be analytically related to each other using a Landau expansion of entropy and free energy, respectively, in analogy with what has been done in (Cohen and Mukamel 2012 J. Stat. Mech .P12017 ). Examples of systems with certain symmetries restricting the Landau expansion have been considered in this reference, while no such restrictions are present in Thirring's model. This leads to a phase diagram that can be seen as a prototype for what happens in systems of particles with kinematic degrees of freedom dominated by long-range interactions.